Non-singleton fuzzy models - Rutkowska, Danuta (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents an approach to design non-singleton fuzzy-logic systems. The relation between non-singleton and singleton fuzzy-logic systems is derived. Simulation results illustrate the effect of uncertainty of the input variables on the truck trajectories in the truck backer-upper control problem.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka